Searching for Housing Model of 21st Century: Analysis of Chosen Polish and Dutch Concepts. (January 2019) - Tokajuk, Andrzej
Abstract: Housing estates play the important role in planning the contemporary European cities. The urban concepts of estates are changing, especially in countries in which there are big housing needs, because fast economic development and sustainable paradigm last decades. The purpose of study is characteristics of the urban concepts and housing environment based on these important examples, chosen by the author: Marina Mokotow Estate in Warsaw, Eko Park Estate in Warsaw and Westerpark Urban District (GWL Terrain) in Amsterdam. The analysis includes: urban composition of mentioned above estates, standards of semi-public spaces, recreational spaces and provided ecological ideas, solutions of the wheeled and walking transport, the quality of architecture. The analysis showed significant differences in urban development of housing estates and the different relations to semi-public spaces and the city space. They represent different typology in creating city planning of 21st century (modernism concept "gated community", mix-used concept based on the city quarters - heterotypic solution and the concept of eco-habitat.